ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DAN PENGUPAHAN INDUSTRI MUTIARA ONIX GAMPING CAMPURDARAT TULUNGAGUNG - Mahendra, Figo Ryan; Winarko, Sigit Puji; Zaman, Badrus; Sugeng (Universitas Nusantara PGRI Kediri, 2025)
This study aims to assess the implementation of Accounting Information Systems (AIS) related to payroll and wages in the Mutiara Onix Natural Stone Industry with a focus on workflow effectiveness, internal control weaknesses, and recommendations for improvement. The research method uses a qualitative case study approach through observation, semi-structured interviews, and review of payroll administration documents. The findings indicate that the payroll process is still carried out semi-manually, recording overtime and deductions is inaccurate, and the separation of functions and authorization is not optimal, thus giving rise to potential errors and misuse. The novelty of the study lies in mapping the needs for integrated digitalization in the small-scale natural stone industry and compiling recommendations based on internal control principles that are in accordance with the characteristics of UMKM.